The effectiveness of football learning model based on assure design in JPOK FKIP UNS students - Umar, Fadilah; Doewes, Rumi Iqbal; Agustiyanto, Agustiyanto (Journal of Education, Health and Sport, 2019)
ASSURE design learning is an altternative learning model that can be done to maximize the role of college students in the learning process by using media and technology as the way. The steps of ASSURE design learning model are through several stage such as: (1) Analyzing characteristic learning, (2) State objectives, (3) Select method, media, and learning materials, (4) Utilize materials, (5) Require learning participations, and (6) Evaluation and revise. Football learning based on ASSURE design is a football learning model with a new conception designed according to the needs and development of JPOK FKIP UNS students. The football learning models based on ASSURE design needs to be compiled and developed so it can be used as a reference for lectures. The ASSURE design based football learning models that have been compiled are (1) Ball Control Learning Model in Football Games based on ASSURE design in JPOK FKIP UNS students. (2) Learning Model of Ball Passing in Football Games based on ASSURE design in JPOK FKIP UNS students. (3) Learning Model of Dribbling Ball in Football Games based on ASSURE design in JPOK FKIP UNS students. (4) Throw-in and Heading Learning Models in Football Games based on ASSURE design in JPOK FKIP UNS students. The purpose of this article is trying to see the effectiveness and use of the ASSURE design model in improving the capability of JPOK Students’ Football Teaching in FKIP UNS.